Peningkatan Representasi Matematis Menggunakan Pembelajaran Ethnomathematics dengan Penerapan Mozart Effect - Dianne Amor Kusuma (IndoMath: Indonesia Mathematics Education, 2020)
This research is driven by the condition of junior high school students in agricultural area of Kabupaten Bandung that shows the mathematical representation abilities of a number of students are still low and they are less motivated to learn mathematics. It is due to the ability of each student in mathematics is not the same and they feel that mathematics learned in school is not used in everyday life, thus impacting on their lack of motivation to learn mathematics. So that students’ mathematical representation abilities can be improved, this research needs to be done. This study aims to determine the differences in increasing students’mathematical representation between those who obtain ethnomathematics learning with the application of Mozart effect (PEM), and students who obtain direct learning (PL). This study used a quasi experimental non equivalent control group design for the 8th grade students of SMPN 1 Bojongsoang, Kabupaten Bandung. The results showed that there were differences in mathematical representation abilities between students who obtained ethnomathematics learning by applying Mozart effect, and students who obtained direct learning. The conclusion of this study is that learning ethnomathematics with the application of the Mozart effect can improve students' mathematical representation abilities.